COMPARATIVE ANALYSIS OF ISSUES OF GENRE, STYLE, SKILL IN THE COVERAGE OF ROAD ESSAYS - Niyozmetov, Bunyodbek (Educational Research in Universal Sciences, 2023)
This article is about the road essay, which is one of the forms of journalism. The issues of genre, style and skill in the coverage of road essays are studied with comprehensive comparative analysis. In addition, to empirical and theoretical methods of knowledge, literary journalism uses some tools of fiction: image and figurativeness, character creation, typification, hyperbole, fable, composite construction, conflict and resolution. The purpose of this is that the facts and opinions about social life that are to be conveyed to the public through these components are not just information, but to influence people’s feelings.